2022
DOI: 10.3389/fphar.2021.789787
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Poor Sperm Quality and Erectile Dysfunction With Oral Pentoxifylline: A Systematic Review

Abstract: Background: Pentoxifylline (PTX) is a member of methylxanthine chemicals and a type of non-selective phosphodiesterase-5 inhibitors, which has been used in male infertility treatment to improve sperm quality and erectile dysfunction (ED) treatment. Mutually tight associations existed between ED and male infertility. Using PTX might kill two birds with one stone by improving sperm quality and erectile function in infertile men with ED.Methods: PubMed, Cochrane Library, EMBASE, and Web of Science were searched b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…It increases the deformability of erythrocytes, reduce blood viscosity, and inhibit fibrotic progression [ 47 , 48 ]. Recent researches also demonstrated that PTX exerted beneficial effects in treating erectile dysfunction, hearing loss, Peyronie’s disease and osteoradionecrosis [ 49 52 ]. As well, in a prospective study, PTX inhibits COVID-19 severity by reduction of IL-6 and c-reactive protein (CRP) and improved prognosis of patients when combined with antioxidants [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…It increases the deformability of erythrocytes, reduce blood viscosity, and inhibit fibrotic progression [ 47 , 48 ]. Recent researches also demonstrated that PTX exerted beneficial effects in treating erectile dysfunction, hearing loss, Peyronie’s disease and osteoradionecrosis [ 49 52 ]. As well, in a prospective study, PTX inhibits COVID-19 severity by reduction of IL-6 and c-reactive protein (CRP) and improved prognosis of patients when combined with antioxidants [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…76 Besides this "pharmacological" effect, pentoxifylline also exerts some pleiotropic "nutraceutical" anti-inflammatory and antioxidant activities. 77,78 As a methylxanthine derivative, it inhibits xanthine oxidase, 79 a key enzyme in purine metabolism that leads to the synthesis of oxidant radicals. Moreover, pentoxifylline exerts direct scavenger activity on ROS 79,80 and blocks their generation by neutrophils in response to proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Pentoxifylline has a specific action of inhibiting phosphodiesterases that degrade cyclic adenosine monophosphate (cAMP), involved, together with its downstream target enzyme, protein kinase A (PKA), in the regulation of sperm axoneme dynein dynamics 76 . Besides this “pharmacological” effect, pentoxifylline also exerts some pleiotropic “nutraceutical” anti‐inflammatory and antioxidant activities 77,78 . As a methylxanthine derivative, it inhibits xanthine oxidase, 79 a key enzyme in purine metabolism that leads to the synthesis of oxidant radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Encouraging results were achieved with one particular analog, PTXm-1, which showed comparable beneficial effect on sperm motility as PTX, even at much lower concentrations, has less effect on sperm acrosome reaction, better sperm DNA integrity, extended sperm longevity and superior embryo quality [ 43 ]. In addition, other phosphodiesterase inhibitors, such as sildenafil, primarily a GMP-specific phosphodiesterase inhibitor, can increase cAMP levels in sperm cells [ 44 ]. A comparison of the usefulness of these different agents is a challenge for future research.…”
Section: Camp As Target Of Therapeutic Action In Human Infertilitymentioning
confidence: 99%